WIMP dark matter candidates and searches—current status and future prospects. (21st May 2018) - Roszkowski, Leszek; Sessolo, Enrico Maria; Trojanowski, Sebastian
Abstract: We review several current aspects of dark matter theory and experiment. We overview the present experimental status, which includes current bounds and recent claims and hints of a possible signal in a wide range of experiments: direct detection in underground laboratories, gamma-ray, cosmic ray, x-ray, neutrino telescopes, and the LHC. We briefly review several possible particle candidates for a weakly interactive massive particle (WIMP) and dark matter that have recently been considered in the literature. We pay particular attention to the lightest neutralino of supersymmetry as it remains the best motivated candidate for dark matter and also shows excellent detection prospects. Finally we briefly review some alternative scenarios that can considerably alter properties and prospects for the detection of dark matter obtained within the standard thermal WIMP paradigm.